2005
DOI: 10.1038/sj.cgt.7700896
|View full text |Cite
|
Sign up to set email alerts
|

The transcription factor Egr1 is a direct regulator of multiple tumor suppressors including TGFβ1, PTEN, p53, and fibronectin

Abstract: Recent studies are reviewed indicating that the transcription factor early growth response-1 (Egr1) is a direct regulator of multiple tumor suppressors including TGFb1, PTEN, p53, and fibronectin. The downstream pathways of these factors display multiple nodes of interaction with each other, suggesting the existence of a functional network of suppressor factors that serve to maintain normal growth regulation and resist the emergence of transformed variants. Paradoxically, Egr1 is oncogenic in prostate cancer. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
285
0
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 325 publications
(296 citation statements)
references
References 83 publications
8
285
0
3
Order By: Relevance
“…Egr-1 can either suppress or enhance tumor development in mouse models and in humans, depending on the molecular context (Baron et al, 2005). Egr-1's tumor suppressor function relies on its ability to induce p53 (Krones- Herzig et al, 2003Herzig et al, , 2005, disabled by SV40T antigen in the RIP1Tag2 model.…”
Section: Resultsmentioning
confidence: 99%
“…Egr-1 can either suppress or enhance tumor development in mouse models and in humans, depending on the molecular context (Baron et al, 2005). Egr-1's tumor suppressor function relies on its ability to induce p53 (Krones- Herzig et al, 2003Herzig et al, , 2005, disabled by SV40T antigen in the RIP1Tag2 model.…”
Section: Resultsmentioning
confidence: 99%
“…EGR1 is an early response gene and can mediate cellular responses to mitogens and growth factors. Such activity is typically associated with oncogenes, but interestingly, Egr1 possesses significant tumor-suppressor properties through its ability to directly regulate key target genes, including TGFb1, PTEN and p53 (TPR53) (Baron et al, 2006). Egr1 þ /À or Egr1 À/À mouse embryonic fibroblasts bypass senescence and, therefore, Egr1 was suggested to be an upstream regulator or 'gatekeeper' of p53-dependent growth regulation .…”
Section: Rps14: a Role For Defective Translation In Mds?mentioning
confidence: 99%
“…7,36 Furthermore, up-regulation of EGR1 can activate other factors involved in apoptosis. It has been reported that EGR1 can up-regulate the expression level of PTEN directly to activate the pro-apoptotic pathway by binding with the PTEN promoter in 293T human fetal kidney cells 37 and in age-related diseases. 12,13 Similarly, EGR1 can also directly induce the transcription of p53 by binding with the p53 promoter in human melanoma A375-C6 cells during thapsigargin-induced apoptosis.…”
Section: Up-regulation Of Egr1 Induces P53 But Not Pten Activationmentioning
confidence: 99%